Implementation of Accounting Standards as an effort to realize the Accountability of Sharia Microfinance Institutions - Naili Saadah (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
Purpose - This study aims to analyze the presentation of the financial statements of what factors influence the presentation of the financial statements of Islamic microfinance institutions according to PSAK 101. Method - This study aims to explore the implementation of accounting standards which are the basis for the presentation of financial statements of Islamic entities, therefore field research with qualitative methods is considered the most appropriate in this study.Result - The results of this study show that in the implementation of accounting standards, sharia people's credit banks have implemented applicable accounting standards while sharia savings and loan cooperatives which are part of sharia entities have not been fully implemented, this is because there are several parts of financial statements that are not presented even though these parts are not crucial, for example zakat infaq and sodaqoh reports some sharia entities do not present because the ZIS levy has been managed by a separate institution so that the reporting is also separate, besides that there are still many human resources who do not understand sharia SAK is an obstacle that is commonly encountered in the field.Implication - Referring to the results of this research, through this research, it is hoped that it will have implications for efforts to improve the competence of financial human resources in order to better understand the applicable accounting standards.Originality - This study seeks to compare the implementation of the presentation of financial statements in several BPRS and BMT and identify weaknesses in the implementation of SAK.